2022
DOI: 10.1007/s00330-022-09269-2
|View full text |Cite
|
Sign up to set email alerts
|

3D CRANI, a novel MR neurography sequence, can reliable visualise the extraforaminal cranial and occipital nerves

Abstract: Objectives We aim to validate 3D CRANI, a novel high-field STIR TSE, MR neurography sequence in the visualisation of the extraforaminal cranial and occipital nerve branches on a 3-T system. Furthermore, we wish to evaluate the role of gadolinium administration and calculate nerve benchmark values for future reference. Methods Eleven consecutive patients underwent MR imaging including the 3D CRANI sequence before and immediately after intravenous gadolinium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Therefore, recent research suggests the suppression of vascular signals by adding a motion-sensitizing T2 preparation prepulse, resulting in a higher contrast-to-noise ratio (CNR) without significantly decreasing SNR in anatomical regions with a close proximity of nerves to vascular structures 32 . On the other hand, Casselman et al showed that cranial nerve imaging (3D CRANI), a novel high-field STIR TSE sequence, with gadolinium www.nature.com/scientificreports/ contrast administration significantly improved suppression quality and nerve visualization in the assessment of extraforaminal cranial nerves 33 . Thus, robust blood vessel suppression, better image quality and fewer artifacts could be achieved for magnetic resonance neurography in various anatomical regions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, recent research suggests the suppression of vascular signals by adding a motion-sensitizing T2 preparation prepulse, resulting in a higher contrast-to-noise ratio (CNR) without significantly decreasing SNR in anatomical regions with a close proximity of nerves to vascular structures 32 . On the other hand, Casselman et al showed that cranial nerve imaging (3D CRANI), a novel high-field STIR TSE sequence, with gadolinium www.nature.com/scientificreports/ contrast administration significantly improved suppression quality and nerve visualization in the assessment of extraforaminal cranial nerves 33 . Thus, robust blood vessel suppression, better image quality and fewer artifacts could be achieved for magnetic resonance neurography in various anatomical regions.…”
Section: Discussionmentioning
confidence: 99%
“…This is the reason why MRI is able to depict soft tissues with a much higher contrast than conventional cross-sectional imaging modalities. Recently, Van der Cruyssen et al and Juerchott et al have shown that by optimizing sequence protocols, direct visualization of small trigeminal branches and even complex structures like the dental pulp is possible, which improves our understanding of nerve physiology in vivo [36][37][38][39]. Furthermore, using T1-based imaging or ultrashort or zero echo time sequences, even the visualization of hard tissues like the mandibular bone and pathological alterations in the course of periodontitis or osteonecrosis has been feasible [9,27,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, computed tomography can only infer pathology of the facial nerve by visualization of erosion or destruction of the adjacent bony facial nerve canal. Although new sequences of magnetic resonance imaging are currently being validated for visualization of the facial nerve (3D Cranio, Casselman et al, and Van Der Cruyssen et al 21 , 22 ), visualization of distal nerve branches is still not possible in this preoperative static imaging modality. Further studies will need to determine the preferred facial nerve imaging modalities.…”
Section: Discussionmentioning
confidence: 99%